2021
DOI: 10.1017/s0142716421000187
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in memory predict changes in breakdown and repair fluency but not speed fluency: A short-term fluency training intervention study

Abstract: The purpose of this intervention study is to reveal the extent to which memory-related aptitudes are implicated in the second language (L2) fluency development fostered by task repetition. English L2 learners are engaged in oral narrative tasks three times per day under two different 3-day task repetition schedules: blocked (Day 1: A-A-A, Day 2: B-B-B, Day 3: C-C-C) versus interleaved (Day 1: A-B-C, Day 2: A-B-C, Day 3: A-B-C). Their phonological short-term memory (PSTM), attention control, and associative mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…A recent line of task repetition inquiry focuses on task repetition schedules, among which the topic of blocked practice and interleaved practice has evoked substantial research interest (Suzuki 2021b). According to Suzuki (2021a), in a blocked condition, each of the practice tasks is repeated in order before moving on to the next task (e.g., AAABBBCCC). While in an interleaved condition, tasks of various types are interspersed (e.g., ABCAB-CABC).…”
Section: Oral Fluency and Task Repetition Schedulementioning
confidence: 99%
“…A recent line of task repetition inquiry focuses on task repetition schedules, among which the topic of blocked practice and interleaved practice has evoked substantial research interest (Suzuki 2021b). According to Suzuki (2021a), in a blocked condition, each of the practice tasks is repeated in order before moving on to the next task (e.g., AAABBBCCC). While in an interleaved condition, tasks of various types are interspersed (e.g., ABCAB-CABC).…”
Section: Oral Fluency and Task Repetition Schedulementioning
confidence: 99%
“…Second, because random assignment of participants to each condition was not feasible in this classroom research, individual differences such as cognitive aptitudes should have been controlled at least statistically. As accumulating evidence suggests that distributed practice effects in L2 grammar learning are moderated by individual characteristics such as working memory and language analytic ability (Kasprowicz et al, 2019;Suzuki, 2019;Suzuki & DeKeyser, 2017b), it is worth exploring possible aptitudeÀtreatment interaction between practice distribution and learners' cognitive aptitude profiles in future research (see Suzuki, 2021a, who demonstrated that some aspects of memory predict the effects of L2 fluency training).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Third, learners can focus on the imitation of nativelike pronunciation forms which is considered to be an important skill for successful L2 speech learning (Flege, Munro, & MacKay, 1995). Fourth, systematic repetition activities can reduce the frequency of dysfluencies and promote the automatization of L2 speech production (Suzuki, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in the classroom setting have pointed to several different types of explicit instruction which can help improve L2 pronunciation proficiency (e.g., Sakai & Moorman, 2018 for high variability perception training; Derwing et al., 2014 for prosody‐based production training; Suzuki, 2021 for fluency training). Although there is a consensus that the provision of explicit instruction (including shadowing and tracking) facilitates adult L2 pronunciation learning, the effect sizes of explicit instruction are relatively small‐to‐medium (e.g., d =.078; Saito & Plonsky, 2019).…”
Section: Introductionmentioning
confidence: 99%